2019
DOI: 10.1101/789784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunotherapy of CT26 murine tumors is characterized by an oligoclonal response against the AH1 tumor rejection antigen

Abstract: The possibility to cure immunocompetent mice bearing murine CT26 colorectal tumors using cytokinebased therapeutics allows to study the tumor rejection process at a molecular level. Following treatment with L19-mIL12 or F8-mTNF, two antibody fusion proteins which preferentially concentrate a murine cytokine payload at the tumor site, CT26 tumors could be cured in a process that crucially relies on CD8+ T cells. In both settings, the AH1 peptide (derived from the gp70 envelop protein of murine leukemia virus) a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…as for cdr3 lengths, the present study showed that applying anti-Pd-1 had no effects on the cdr3 lengths of the Tcr/Bcr repertoires. Similarly, cytokine-based immunotherapy of murine cT26 colorectal tumors did not lead to significant changes of CDR3 length distribution (38). In addition, it has been reported that there is no correlation between the cdr3 length distributions and genetic variability of the cdr3 region (39), suggesting that the repertoire divergence between the treatment and control group in this study is not represented in terms of cdr3 length.…”
Section: Discussionmentioning
confidence: 44%
“…as for cdr3 lengths, the present study showed that applying anti-Pd-1 had no effects on the cdr3 lengths of the Tcr/Bcr repertoires. Similarly, cytokine-based immunotherapy of murine cT26 colorectal tumors did not lead to significant changes of CDR3 length distribution (38). In addition, it has been reported that there is no correlation between the cdr3 length distributions and genetic variability of the cdr3 region (39), suggesting that the repertoire divergence between the treatment and control group in this study is not represented in terms of cdr3 length.…”
Section: Discussionmentioning
confidence: 44%